Profile detection through source code static analysis - Novais, Daniel (2016)
The present article reflects the progress of an ongoing master’s dissertation on language engineering. The main goal of the work here described, is to infer a programmer’s profile through the analysis of his source code. After such analysis the programmer shall be placed on a scale that characterizes him on his language abilities. There are several potential applications for such profiling, namely, the evaluation of a programmer’s skills and proficiency on a given language or the continuous evaluation of a student’s progress on a programming course. Throughout the course of this project and as a proof of concept, a tool that allows the automatic profiling of a Java programmer is under development. This tool is also introduced in the paper and its preliminary outcomes are discussed.